Restricted Growth Clinical, Genetic and Molecular Aspects - del Carmen Cardenas- Aguayo, Maria (IntechOpen, 2016)
Restricted growth conditions are a group of genetic disorders with primary effect on growth (short stature); it is very heterogeneous and comprises two important categories: skeletal dysplasia and different genetic syndromes with primary effect on growth. It could also be caused by a medical condition. The book contains chapters regarding different aspects of the study of restricted growth that are divided into three broad sections. Section I: Defining Restricted Growth, Section II: Genetics and Diagnosis of Restricted Growth, and Section III: Signaling Pathways and Molecular Mechanisms of Restricted Growth. The book presents comprehensive reviews of each topic written by experts in the field. It will be the most valuable tool for physicians and life science researchers and students. We hope that the book will motivate discussion and research in this important health problem, setting the path for better therapeutic approaches.